1986
DOI: 10.1071/mf9860595
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of the nisto stage of Scyllarus demani Holthuis, two unidentified Scyllarus species, and the juvenile of Scyllarus martensii Pfeffer (Crustacea : Decapoda : Scyllaridae), reared in the laboratory; and behavioural observations of the nistos of S. demani, S. martensii and Thenus orientalis (Lund)

Abstract: Descriptions of the Nisto Stage of Scyllarus demaniHolthuis, Two Unidentified Scyllarus Species, and the Juvenile of Scyllarus martensii Pfeffer (Crustacea : Decapoda : Scyllaridae), Reared in the Laboratory; and Behavioural Observations of the Nistos of S. demani, S. martensii and Thenus orientalis (Lund) Live final-stage phyllosoma larvae of 7. orientalis, S. martensii, S. demani, and an unidentified specimen, Scyllarus sp. A, were obtained from the mid-shelf region of the Great Barrier Reef. While held in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The postlarval nisto provides the link between the planktonic and benthic life-history phases in scyllarids, as does the puerulus in palinurids. However, Barnett et al (1986) suggest that in some species (e.g., T. orientalis) the nisto is much closer to the adult form than is the nisto of other scyllarid species (or the puerulus of palinurids), and its functional role may not, therefore, be identical in all species. The great range in nisto size (3-21 mm CL; Table 1), not in direct proportion to the size of the final phyllosoma instar, would be consistent with this.…”
Section: Postlarval Phasementioning
confidence: 94%
See 4 more Smart Citations
“…The postlarval nisto provides the link between the planktonic and benthic life-history phases in scyllarids, as does the puerulus in palinurids. However, Barnett et al (1986) suggest that in some species (e.g., T. orientalis) the nisto is much closer to the adult form than is the nisto of other scyllarid species (or the puerulus of palinurids), and its functional role may not, therefore, be identical in all species. The great range in nisto size (3-21 mm CL; Table 1), not in direct proportion to the size of the final phyllosoma instar, would be consistent with this.…”
Section: Postlarval Phasementioning
confidence: 94%
“…Medusa-riding does not appear to be accidental or entirely intermittent: Herrnkind et al (1976) observed 80 Scyllarus sp. larvae on 402 individual Aurelia aurita examined; and Barnett et al (1986) found 49 out of 51, mostly final stage phyllosomas of Thenus orientalis, P. demani, Eduarctus martensii, and a Scyllarus sp. collected, to be closely associated with medusae.…”
Section: Phyllosoma Biologymentioning
confidence: 99%
See 3 more Smart Citations